No labirinto de gaia: representações sociais construídas no Instituto Federal de Educação, Ciência e Tecnologia do Maranhão sobre Educação Ambiental - RODRIGUES, Hadryan Lima (2024)
This study is part of the research developed in the Graduate Program in Education (PPGE), Doctorate in Education, at the Federal University of Maranhão (UFMA), focusing on Environmental Education practiced at the Federal Institute of Education, Science, and Technology of Maranhão (IFMA). It is based on the Theory of Social Representations (TRS), inaugurated by Moscovici in 1961, due to the convergence between the theoretical principles of this theory and the object of study. The research is guided by the following questions: What are the social representations constructed by the teachers of the Technical Course in Environment at the Federal Institute of Maranhão regarding Environmental Education? How do these representations guide the educational and socio environmental practices in the Technical Course in Environment? The study aims to understand how teachers of the Technical Course in Environment at the Federal Institute of Maranhão construct social representations about Environmental Education and their psychosocial implications for educational and socio environmental practices. Regarding the methodological procedure, the research is qualitative in nature and utilizes three approaches: bibliographic, documentary, and empirical. The IFMA São Luís Centro Histórico campus was chosen as the research locus, with the sample consisting of teachers from this campus. Content analysis, as proposed by Bardin (1977), was used to analyze the information contained in the cited documents and data collected through semi-structured interviews conducted and a profile questionnaire administered to the teachers. The research reveals representational evidence on: the approach to Environmental Education within the PPI, which suggests an integrated view of human beings, recognizing their complexity and interconnectedness with historical-cultural aspects and the environment; the specifications of the Technical Course in Environment Curriculum Plan, which guide the curriculum development and teachers’ pedagogical practices; and the perceptions expressed in the participants’ statements, indicating representations that may redirect practices, objectives, and strategies related to Environmental Education in IFMA’s daily activities. The study also highlights the construction of multifaceted social representations of Environmental Education, anchored in diverse meanings. These range from how individuals interpret the importance of institutional documents, such as the PPI and PCTMA, to how they perceive the daily context in which their teaching activities are carried out.